Chitin nanofibrils modulate mechanical response in tympanic membrane replacements. (15th June 2023) - Anand, Shivesh; Azimi, Bahareh; Lucena, Mónica; Ricci, Claudio; Candito, Mariarita; Zavagna, Lorenzo; Astolfi, Laura; Coltelli, Maria-Beatrice; Lazzeri, Andrea; Berrettini, Stefano; Moroni, Lorenzo; Danti, Serena; et al.
Abstract: The tympanic membrane (TM), is a thin tissue lying at the intersection of the outer and the middle ear. TM perforations caused by traumas and infections often result in a conductive hearing loss. Tissue engineering has emerged as a promising approach for reconstructing the damaged TM by replicating the native material characteristics. In this regard, chitin nanofibrils (CN), a polysaccharide-derived nanomaterial, is known to exhibit excellent biocompatibility, immunomodulation and antimicrobial activity, thereby imparting essential qualities for an optimal TM regeneration. This work investigates the application of CN as a nanofiller for poly(ethylene oxide terephthalate)/poly(butylene terephthalate) (PEOT/PBT) copolymer to manufacture clinically suitable TM scaffolds using electrospinning and fused deposition modelling. The inclusion of CN within the PEOT/PBT matrix showed a three-fold reduction in the corresponding electrospun fiber diameters and demonstrated a significant improvement in the mechanical properties required for TM repair. Furthermore, in vitro biodegradation assay highlighted a favorable influence of CN in accelerating the scaffold degradation over a period of one year. Finally, the oto- and cytocompatibility response of the nanocomposite substrates corroborated their biological relevance for the reconstruction of perforated eardrums. Graphical abstract: Unlabelled Image